Risky Mothers and the Normalcy Project: Women with Disabilities Negotiate Scientific Motherhood. (February 2017) - Frederick, Angela
Feminist scholars have been critical of the expectations placed upon mothers to accomplish a perfect version of motherhood, but have often failed to interrogate the values about normalcy and disability imbedded in modern mothering ideologies. Mothers with disabilities are well positioned to expose the underlying beliefs about normalcy with which all mothers must contend. Drawing from interviews and focus groups conducted with mothers who have physical and sensory disabilities, I explore Deaf/disabled women's experiences negotiating the scientific motherhood regime. Illuminating a paradox, I argue these women are labeled "risky mothers" under scientific motherhood, which prizes the management of risk and the prevention of disability. Yet, these mothers are simultaneously rendered invisible by inaccessible and inflexible medical practices, and by a consumer market of expert advice which prescribes that mothers inhabit a typical body. These women's experiences illuminate the normalcy project as a central tenet of scientific motherhood.